THE EFFECT OF REPEATED READING STRATEGYIN ENANCHING STUDENTS READING ACHIEVEMENT - Indra Pratama (Journal of English Teaching and Learning, 2021)
The effect of repeated reading strategyin enanching student reading achievement ). This study aims to improve reading comprehension skills in the students' achievement of class XI Culinary 2 Smk Sritanjung Banyuwangi. ability using the poster achievement technique.The action research was conducted in two classes, namely class control and experiment. Actions given to students in the form of the application of the post-test score method of students 'speaking ability were analyzed using the independent sample t-test through the SPSS 25 program to improve students' reading comprehension skills. Data collection techniques in the form of observation, tests, and documentation.The data analysis technique used qualitative and quantitative descriptive analysis.Qualitative analysis is used for qualitative data in the form of interviews, field notes,and documentation of student assignments The results of this study are in accordance with the objectives of the repeated reading strategy, namely help students explore curiosity. In addition, read over and over also aims to help students to find problems in reading, improve student skills in analyzing the content of the reading text, with making students' mind mapping easier to analyze reading. Study that conducted by Alpar Murat (2015) score of deviation for control group is 6.086 and experimental group is 5.224. Then , the result of t-test founded 0,00 as the significant. So, the researcher continued to count the degree of freedom in order to know the data was significant or not. Afterwards, comparison between t-table and significant level 5% (0,05) indicated that 0,00<0,05, which means that it was significant. that repeated reading implementation brought positive impact to the student’s reading disability. It was detected by the post test score that increased in each session of the reading.However, the passagge sorting process is also influence the students’ reaction towards each reading session.In addition,the finding of the research shown that in the second reading session, four of eight students increased their reading score, and the other four students steady in their score. It means, the implementation of repeated reading was likely success. English teachers use repeated reading strategies as one of them alternatives in teaching reading to their students since learning English Through repeated reading with the text is a great and enjoyable activity for them. That can improve their reading fluency in order to know more about learning English, especially in learning to read, changing their view that learning to read itself something fun and not boring and tense.Researchers then discuss other functions of reading strategies to be applied in the teaching and learning process in the future